Composition and richness of monogonont rotifers from La Plata River Basin, South America - Martins, Barbara A. [UNESP]; Coelho, Paula N. [UNESP]; Nogueira, Marcos G. [UNESP]; Perbiche-Neves, Gilmar (Revista Biota Neotropica, 2020)
We present here the first study that analyzed the composition and richness of rotifers of the entire La Plata River basin, the second largest in South America, based on simultaneous and standardized sampling. Fifteen large reservoirs and eight river stretches were selected in the upper, middle, and lower portions of the Parana, Paraguay, and Uruguay Rivers, which are the major rivers of the La Plata basin. We took a total of 86 samples (open water habitats) in 2010. A mean of 27 +/- 11 species per sub-basin was found, with the highest richness in the Lower Parana (41 species), followed by the Paranapanema (40 species) and Lower Uruguay (38 species). Low richness was observed in the Middle Uruguay and Middle Parana. We found 106 species belonging to 21 families and two orders. The family with the highest number of species was Lecanidae (21), followed by Brachionidae (20), Trichocercidae (9), and Synchaetidae (8). The species with higher occurrences were Conochilus dossuarius, Kellicottia bostoniensis, Keratella americana, Keratella cochlearis and Hexarthra mira. New occurrences of rotifers were registered for Brazil (Colurella adriatica), Sao Paulo State (Enteroplea lacustris), and Argentina (Gastropus hyptopus, Harringia rousseleti and Lecane thienemanni). Spearman correlation between the number of species and physical and chemical variables demonstrated positive correlation with chlorophyll and temperature, and negative correlation with dissolved oxygen. We extend the distribution list for some native (Lecane ludwigii) and non-native species of rotifers (K. bostoniensis). We also list the monogonont rotifer species found at the sampling stations.
Keywords: Biodiversity; Rotifera; Survey; New records; Lotic; Lentic environments